Прилучення новонародженого до сакрального - Штюке, Н. (Народна творчість та етнологія, 2011)
The birth is a decisive moment both for the child’s existence, for his family and even for all community. The new-born was considered impure and dangerous, but vulnerable in the same time. The midwife’s role is of paramount importance, as initiated person and mediator, who performs the protection and integration gestures and acts and who has the ability (especially in the latest period) of influencing the new-born and interpreting his birth signs (the day, the weather, bodily marks, the cry).